Solve the system of equations graphically. Write your answer as an ordered pair (x,y). 6x ‒ 3y = 12 y = x ‒ 2

(1) Answers

ok so basically we have to plug in y with what they give us so 6x-3(x-2)=12 lets solve once we plugged in y . ok so 6x-3x+6=12 now we subtract 6x from 3x which results in 3x+6=12 now we do the opposite of 6 which is to subtract 6 from both sides . 12-6=6  now we are left with 3x=6 which is 2 . so we solved for x now lets solve for y ok? We are going to do the same thing like on the other question so 2-2 =0 your answer is (2,0)

Add answer